Expression 1: "f" left parenthesis, "R" , right parenthesis equals Start sum from "n" equals 1 to "R" , end sum, left parenthesis, negative 1 , right parenthesis Superscript, "n" , Baseline Start sum from "x" equals 1 to "n" , end sum, left brace, mod left parenthesis, "n" , "x" , right parenthesis equals 0 : left parenthesis, negative 1 , right parenthesis Superscript, "x" , Baseline "x" cubed , 0 , right bracefR=R∑n=1−1nn∑x=1modn,x=0:−1xx3,0
1
"x" Subscript, 1 , Baselinex1
"f" left parenthesis, "x" Subscript, 1 , Baseline , right parenthesisfx1